The Effect of Motivation on Employee Performance at the Social Service, Manpower and Transmigration, Maros Regency, South Sulawesi, Indonesia - Arifai, Muh.; Muammar, Muammar (PINISI Discretion Review, 2022)
This study aims to determine the magnitude of the effect of motivation on employee performance at the Department of Social Affairs, Manpower and Transmigration Maros Regency . Theoretically, the results of this study are expected to develop scientific treasures and establish well-coordinated human relationships and roles in the field of human resources in the hope of making a contribution that leads to improving agency performance, through the application of motivation for social services, labor and transmigration in Maros Regency. The variables in this study are the motivational variable as the dependent variable, while the performance variable as the independent variable. The data collection technique uses observation and questionnaire methods as well as being the sample in this study as many as 53 employees. The results of this study indicate that partially the motivational variable has a significant positive effect, while simultaneous testing shows a significant positive effect on the performance of social service employees, labor and transmigration in Maros Regency. The coefficient of determination indicates that the ability of the independent variable to predict the influence of motivation has a moderate effect on employee performance. Therefore, it is necessary to pay attention to the provision of motivation by the leadership, especially the Head of the Social Service of Manpower and Transmigration in Maros Regency so that employees are more enthusiastic about working.